Internationalization of Higher Education in Russia: in Search for Development - E. V. Nikitenko (Высшее образование в России)
The aim of the article is to identify ways and conditions for internationalization development in Russia. The author shows from the neo-institutional approach point of view that Western internationalization strategies are implemented under conditions of the formed university identity as an entrepreneurial one with strong institutional support. At the present moment, in Russia new university’s identity is still the forming, such a system of education at the institutional level is absent. It was also noted, that internationalization in the West was initially used as a tool to improve the quality of education that perspectively contributed to higher school competitiveness under conditions of mass-market orientation. While in Russia university’s competitiveness is a condition for successful internationalization. At the present formal changes in the education system, informal limitations create a conflict for the university identities. The university is still not perceived as a sovereign economic entity. The market capacity factor is poorly taken into account. The entrepreneurial component of higher education institution does not act as its competitive advantage at this stage, and in the global dimension its significant lag is observed. Important conditions for the successful development of internationalization are: a differentiated approach to universities in the implementation of internationalization strategies, the relative autonomy of the university, the elimination of the gap between the goals of internationalization and state mechanisms aimed at their implementation, as well as the conditions for developing internal internationalization, the interested joint activity of all subjects of the scientific and educational process and the private sector of the economy, the elimination of the gap among the developed mechanisms for increasing the competitiveness of the university through the commercialization of projects and the underdevelopment of public private partnership (PPP) forms in the higher education system, improving approaches to organizing the scientific and educational activities of the university.